Rare case of primary carnitine deficiency presenting as acute liver failure. Issue 7 (19th July 2022) - Jain, Shalu; Kumar, Karunesh; Malhotra, Smita; Sibal, Anupam
Abstract : Systemic primary carnitine deficiency (PCD) is an autosomal recessive disorder caused by mutations in the SLC22A5 gene that encodes carnitine transporter, OCTN2. Transporter deficiency leads to defective fatty acid oxidation. Signs and symptoms ranging from liver injury in children to cardiomyopathy and skeletal myopathy in adults, manifest during periods of stress and fasting. Though acute liver failure is infrequently described, young children presenting as acute liver failure should be screened for fatty acid oxidation defects including PCD by testing plasma for amino acids and further confirmed by genetic sequencing. Early identification and treatment using L-carnitine is lifesaving. Our patient presented as acute liver failure and diagnosis of PCD was confirmed by metabolic screening and genetic sequencing. He responded to the treatment.